Newly qualified teachers' perceptions and experiences about portfolio assessment in Wa Municipality, Ghana - Paul Akumdaare Atiah (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2023)
Portfolio assessment is a tool that enables professionals to reflect on their development. Despite the popularity of portfolio-based assessment among educators, little research has been conducted in Ghana to establish how newly trained teachers view portfolio assessment as a learning and assessment tool. A survey of newly qualified teachers was performed to learn about their experiences and perceptions of portfolio assessment as a tool for continuing professional development (CPD) and obtaining a full teaching license in Wa Municipality, Upper West Region of Ghana with a total population of 187. Out of the total population,58 newly qualified teachers (NQTs) were selected using a simple random sampling procedure. The researcher used a questionnaire as the predominant instrument to obtain data. Quantitative data were analyzed using descriptive statistics such as tables, charts, and bar graphs. Qualitative data were also analyzed using content analysis. This was based on analysis of meaning and implications emanating from the respondents' information. The portfolio was deemed a good learning tool by the majority of the research participants, the newly qualified teachers. They did, however, believe that creating a proper portfolio is stressful and time-consuming. According to the study's findings, the system will not succeed unless students receive proper direction from academic professionals like National Teaching Council (NTC), in-service teachers, and headteachers, etc.